Patient-specific reconstruction utilizing computer assisted 3D modelling for partial bone flap defect in hybrid cranioplasty - Hueh, Low Peh (2017)
Background: Autologous cranioplasty using a patient’s original bone flap remain the commonest practice nowadays. However, partial bone flap defect is commonly encountered. Replacing the bone flap with pre-moulded synthetic bone flap is costly and might not be affordable for all patients. Hence, some small to medium size defects were topped up with alloplastic material on a free hand basis intra-operatively that often resulted in inaccurate implant approximation with unsatisfactory cosmetic result. This rationale the need for an alternative technique for reconstruction of partial bone flap defect in cranioplasty. The objective of this study is to evaluate implant accuracy and cosmetic outcome of cranioplasty candidates with partial bone flap defect who underwent reconstruction utilising computer assisted 3D modelling.